2022
DOI: 10.21037/atm-22-1193
|View full text |Cite
|
Sign up to set email alerts
|

Association between chronic illness resources and health behaviors in hypertensive stroke patients at 6 months after discharge: a cross-sectional study

Abstract: Background: The adoption of appropriate health behaviors can prevent the recurrence of stroke. Previous research found a downward trend in hypertensive stroke patients' health behaviors from 3 to 6 months after discharge. The provision of appropriate support by chronic illness resources has been shown to predict patients' engagement in appropriate health behaviors in other chronic illness populations. This study sought to explore the association between chronic illness resources and health behaviors in hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…In this study, chronic illness resource was found to have the most significant direct effect on health behaviour. This finding corresponds with previous study (Wen et al, 2022). Zhong et al (2016) found that the use of chronic illness resources of patients with diabetes was positively correlated with the self‐management including diet, exercise, medicine, glucose monitoring, foot care and dealing with hyperglycaemia and hypoglycaemia.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this study, chronic illness resource was found to have the most significant direct effect on health behaviour. This finding corresponds with previous study (Wen et al, 2022). Zhong et al (2016) found that the use of chronic illness resources of patients with diabetes was positively correlated with the self‐management including diet, exercise, medicine, glucose monitoring, foot care and dealing with hyperglycaemia and hypoglycaemia.…”
Section: Discussionsupporting
confidence: 94%
“…The Chronic Illness Resources Survey (CIRS) is compatible with a social-ecologic perspective to assess distal sources of support, including workplace, community, media, public policy, and neighbourhood factors (Glasgow et al, 2000). In addition, a cross-sectional study (Wen et al, 2022) showed that the chronic illness resource has a positive association with health behaviour in hypertensive stroke patients. Therefore, institutional, community and public policy factors were unified as environmental factors in this study and measured by CIRS.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The social–ecological pyramid model illustrates the interrelationships between individual/interpersonal factors and multilevel social resources, such as family/friends, physician/health‐care team, peer, community/neighbourhood, media/policy, worksites and organizations. Related studies have verified the impact of multilevel social resources on self‐management behaviour and health outcomes of patients with chronic diseases (Glasgow et al, 2000;Wen et al, 2022). But in regard to diabetes social resource interventions, the few studies that are available are more focused on strengthening social resources at the individual level and examining its effect on single behaviours such as dietary habits (Caperon et al, 2019) or physical activity (Soderlund, 2017).…”
Section: Introductionmentioning
confidence: 88%
“…One common problem is that traditional DSME is didactic in resources on self-management behaviour and health outcomes of patients with chronic diseases (Glasgow et al, 2000;Wen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%